Comparative Study on Cancer Yielding Rate Between sextant vs Ten Cores TRUS Biopsy - Shahjamal, Sharif; Rahman, Md Afzalur; Saha, Prodyut Kumar; Sultana, Rayhana; Naser, Md Fazal; Alam, SM Mahbub (Bangladesh Journal of Urology, 2022)
Background: The standard sextant biopsy protocol misses about 15% of cancer when compared with results obtained from a more extensive biopsy procedure. The number of systematic biopsies has increased over the years, with 10–12 cores currently accepted as the minimum standard. Objectives: To compare the detection rate of carcinoma prostate through standard sextant biopsy and extended 10-core biopsy in Bangladeshi male subjects. Methods: This prospective experimental study was conducted in the Department of Urology of Dhaka Medical College Hospital, Dhaka from January 2007 to May 2008 including a total of 69 male patients aged over 56 years having normal digital rectal examination (DRE) findings with serum PSA level of 4 ng/mL or greater or having abnormal findings on DRE irrespective of serum PSA level. The subjects underwent transrectal ultrasound (TRUS) and biopsies were taken systematically. Biopsy results were interpreted according to different sextant biopsy protocols and also following extended 10-core biopsy protocol. Data collection sheet containing the selected points were filled up. Data were analysed using SPSS version 12. The test statistic used to analyse the data were descriptive statistics and McNemar’s test. The level of significance was set at 0.05 and p <0.005 was considered significant. Result: Out of the total 69 subjects, 29 (42%) were diagnosed to have prostate cancer following biopsy. In the standard mid lobar sextant protocol the cancer detection was lowest (79.3%) while it was highest (89.7%) when lateral zone biopsy was performed. The extended 10-core biopsy regimen had higher cancer detection rate than any of the standard sextant protocols and it was 96.6%. The difference in the cancer detection rates between the two schemes was statistically significant (p <0.001). Conclusion: The sextant biopsy is inadequate in detecting carcinoma prostate and extended 10-core biopsy protocol including the apex, midlobar mid gland, lateral mid gland and lateral base with more extensive sampling of the lateral aspects of the prostate is superior. Bangladesh J. Urol. 2021; 24(2): 214-219